Spontaneous utero-rectal fistula formation following reconstructive genital tract surgery: An interesting case report - Ghose, Seetesh; P, Pallavee; Samal, Rupal; V, Ashwini (Indian Journal of Case Reports, 2019)
A genital fistula is an abnormal communication between uterus with either urinary tract or gastrointestinal tract. Although genitourinaryfistula is a common entity, rectovaginal or even uterorectal fistula is relatively uncommon. The etiology of fistula is usually due toan obstetric cause in a developing country, whereas, it is gynecological in the developing country. Whether etiology is obstetricalor gynecological, this develops following days of the procedure. Here, we present the case of a 17-year-old girl, who underwentvaginoplasty for cervical atresia and develop uterorectal fistula one and a half year following the first surgery. She was finallymanaged with hysterectomy.